The optimal choice of after-tax and pre-tax performance measures in the presence of tax base risks - Jens Robert Schöndube; Alexandra Spaeth (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2024)
In practice, both pre- and after-tax performance measures are used to incentivize managers. In this paper, we analyze the optimality of these performance measures in an agency setting, assuming that both the principal and the agent face tax base risks. Switching from a pre-tax to an after-tax measure introduces a risk effect, including an additional variance and a covariance effect, both of which stem from the principal's tax base risk. We show that the after-tax measure is the optimal performance measure if and only if the negative covariance effect dominates the variance effect. If the principal can evade taxes, there is a tax evasion effect in addition to the risk effect, which captures the distortion of tax evasion under the after-tax measure. Now, using the after-tax measure is only optimal, if the weighted risk effect is stronger than the tax evasion effect. Tax revenue may not be maximized by using the optimal performance measure if the agent's tax base risk and the firm's cash flow are positively correlated. While the pay-performance sensitivity of the optimal contract is independent of tax avoidance under the pre-tax measure, under the after-tax measure it is decreasing with increasing incentives for sheltering. If tax evasion is possible, lower levels of tax evasion under the after-tax measure result in an increase in tax revenue relative to the pre-tax measure. The results of our study have implications for contract design, tax political actions and tax revenues.
Keywords: 330; agency theory; performance measures; taxation; tax evasion; tax base risk